Wide Variation in the Use of Radiotherapy in the Management of Surgically Treated Rectal Cancer Across the English National Health Service. Issue 8 (August 2016) - Morris, E.J.A.; Finan, P.J.; Spencer, K.; Geh, I.; Crellin, A.; Quirke, P.; Thomas, J.D.; Lawton, S.; Adams, R.; Sebag-Montefiore, D.
Abstract: Aims: Radiotherapy is an important treatment modality in the multidisciplinary management of rectal cancer. It is delivered both in the neoadjuvant setting and postoperatively, but, although it reduces local recurrence, it does not influence overall survival and increases the risk of long-term complications. This has led to a variety of international practice patterns. These variations can have a significant effect on commissioning, but also future clinical research. This study explores its use within the large English National Health Service (NHS). Materials and methods: Information on all individuals diagnosed with a surgically treated rectal cancer between April 2009 and December 2010 were extracted from the Radiotherapy Dataset linked to the National Cancer Data Repository. Individuals were grouped into those receiving no radiotherapy, short-course radiotherapy with immediate surgery (SCRT-I), short-course radiotherapy with delayed surgery (SCRT-D), long-course chemoradiotherapy (LCCRT), other radiotherapy (ORT) and postoperative radiotherapy (PORT). Patterns of use were then investigated. Results: The study consisted of 9201 individuals; 4585 (49.3%) received some form of radiotherapy. SCRT-I was used in 12.1%, SCRT-D in 1.2%, LCCRT in 29.5%, ORT in 4.7% and PORT in 2.3%. Radiotherapy was used more commonly in men and in those receiving an abdominoperineal excision and less commonly in the elderly and those with comorbidity. Significant and substantial variations were also seen in its use across all the multidisciplinary teams managing this disease. Conclusion: Despite the same evidence base, wide variation exists in both the use of and type of radiotherapy delivered in the management of rectal cancer across the English NHS. Prospective population-based collection of local recurrence and patient-reported early and late toxicity information is required to further improve patient selection for preoperative radiotherapy. Highlights: Wide variation exists in both the use of and type of radiotherapy delivered in the management of rectal cancer. Population-based capture of local recurrence and toxicity information are required to further improve patient selection.